The vibroacoustical research of roll bearings defects - Juodzevičius, Eimantas (Transport, 2003)
This article presents the description, results and conclusions of the methodology of the vibroacoustical research of the transmission of one of the units of a tactical car – of the bevel bearings of the main gear reducer. To explore the vibroacoustical research of the roll bearings with reference to the latest western literature the main diagnostic methods are used. Their advantages and disadvantages, the limits of the vibration frequencies, where the assessment of acoustical parameters of vibration, are analyzed. The defects of the bearings are identified exploring the level of the noise intensiveness in the proximate points fiom the bearings, components (changing the diametric clearance), and the results are presented in the form of the spectra of the amplitude surrounding.First Published Online: 19 Dec 2011